V-ATPases and Their Implication in Oral Cancer - Oliveira Alves, Monica Ghislaine [UNESP]; Garcia-Garcia, Abel; Perez-Sayans, Mario; Chakraborti, S.; Dhalla, N. S. (Springer, 2016)
The control of intracellular and extracellular pH is extremely important for many biological functions and the condition of hypoxia is a frequent phenomenon during the development of oral squamous cell carcinoma (OSCC). The cellular acidosis appears to be controlled, mainly, by the vacuolar-type H+ ATPase (V-ATPase), which is clearly involved in cellular transformation during carcinogenesis and metastasis. The C subunit (ATP6V1C) of V1 intra-membrane domain of the V-ATPase is primarily responsible for its enzymatic function, through the control of a reversible dissociation of VO and V1 domains. It is observed a high overexpression of the gene ATP6V1C 1 in OSCC, this tumor cells exhibited high metabolic activity and the active mechanisms capable of pumping protons from the cell interior are necessary. The acidification of the extracellular environment resulting from poor vascularization and cell metabolism promotes the activity of proteolytic enzymes that contribute to tumor invasiveness and metastasis. In the future, V-ATPase inhibitor molecules could be used in cancer treatment through the mensuration of the overexpression of specific V-ATPase subunits in tumors to be treated and, then, using specific inhibitors for the subunits being expressed. This will allow clinicians to provide more specific treatment, while also minimizing adverse effects.
Keywords: Oral squamous cell carcinoma; ATP6V1C1; Cancer; V-ATPase inhibitors; Tumor metastasis; Chemoresistance